The Essential World History, 8th Edition - William J. Duiker; Jackson J. Spielvogel (Cengage Learning, 2016)
Explore world history in a brief, balanced, highly readable overview that examines common challenges and experiences that unite the human past and identify key global regional patterns over time with THE ESSENTIAL WORLD HISTORY. This brief overview of world history covers political, economic, social, religious, intellectual, cultural, and military history integrated into a chronologically ordered synthesis to help you gain an appreciation and understanding of the distinctive character and development of individual cultures in society. You can use the book's global approach and its emphasis on analytical comparisons between cultures to link events together in a broad comparative and global framework that places the contemporary world in a more meaningful historical context.